Efficacy of Selected Biopesticides with Chlorantraniliprole against Gram Pod Borer, Helicoverpa armigera (Hubner) on Chickpea - Dayma, Shubham; Tayde, Anoorag Rajnikant; Tripathi, Akhilesh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present investigation was conducted at the research plot of Department of Entomology at CRF, Sam Higginbottom University of Agriculture Technology and Sciences, Prayagraj during the Rabi season of 2023-2024. The experiment was conducted in Randomized Block Design (RBD) using eight treatments each replicated thrice viz., Neem oil 2 % @20ml/lit, Spinosad 45 % SC @0.3ml/lit, NSKE 5% @5ml/lit., Bacillus thurngiensis @2.5 gm/lit, Beauveria bassiana @2.5gm/lit, Emamectin benzoate 5%SG @2ml/lit, Chlorantraniliprole18.5 S @1.5ml/lit and untreated control. Among the biopesticides and insecticides evaluated, Chlorantraniliprole 18.5 SC recorded lowest mean population of pod borer population i.e. (1.79) which was significantly superior over control followed by Spinosad 45 % SC (2.02%), Emamectin benzoate 5%SG (2.23%), Neem oil 2% (2.41%), NSKE 5% SC (2.61%), Bacillus thurngiensis (1.83%) and Beauveria bassiana (2.99%) was least effective among all the treatments. Among the treatment studied the best and most economical treatment was Chlorantraniliprole 18.5SC with highest and cost benefit ratio of 28.3 q/h and 1:3.1 followed by Spinosad 45 % SC %SC 26.7 q/h, 1:3.0, Emamectin benzoate 5%SG 25.8q/h and 1:2.9, Neem oil 2 % 22.5 q/h, 1:2.4, NSKE 5% 21.2 q/h , 1:2.2, Bacillus thurngiensis 17.0 q/h, and 1:1.9, Beauveria bassiana 11.7 q/h, and1:1.2 as compared to control 9.3 q/h and 1:1.1.